The generalized three-component hybrid model of the content of teaching elements of electrical equipment - Lazarev, N.; Mosiienko, H.; Tarasenko, A. (Problems of Engineer-Pedagogical Education, 2019)
The article deals with the problem of forming a generalized model of the content of teaching elements of electrical devices of industrial equipment based on a systems approach. Based on the analysis of the literature sources on electrical engineering training of non-electrical specialties, it is shown that the result of theoretical and practical training of future engineers should consist in their ability to choose the necessary electrotechnical, electronic, electrical measuring devices, to operate them properly and to create, together with electrical engineers, technical specifications on the development of electrical parts of automated production equipment for managing production processes. It is shown that all physical elements of real electrical circuits used in industrial equipment have signs of basic electrical parameters. Electrical parameters are characterized by those physical phenomena that cause the processes occurring in them. Each physical element of a real subject area can be represented as a specific connection of a certain set of ideal elements. The representation of physical elements in design schemes depends on the frequency of the alternating current. But all the complexity of the physical processes occurring in AC circuits should not necessarily be taken into account in every single case. You can make a number of assumptions that greatly simplify the task and at the same time do not lead to noticeable deviations from reality. The importance of building generalized models of real elements of electrical devices of industrial equipment based on the most common types of modeling, which are used in technical theories, is substantiated. The considered approach to the formation of a three-component model of the elements and devices of electrical equipment can be used to build a model of any educational element of the content of electrical engineering education. This method makes it possible to formalize the modeling process by combining its main fragments based on the proposed system approach.